2020
DOI: 10.1186/s12917-020-02467-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and genome analysis of feline morbillivirus in household and shelter cats in Thailand

Abstract: Background: Feline morbillivirus (FeMV) has been discovered in domestic cats associated with tubulointerstitial nephritis, but FeMV is also detected in healthy cats. This research aimed to identify and characterize the FeMV strains detected in a Thai cat population. Results: Two-hundred and ninety-two samples (131 urine and 161 blood) derived from 261 cats (61 sheltered and 200 household cats) were included for investigating the FeMV prevalence using real-time reverse transcription PCR. The overall prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 34 publications
0
37
1
Order By: Relevance
“…In 2009, feline morbillivirus (FeMV) was isolated for the first time from stray cats ( Felis silvestris catus ) in Hong Kong [ 1 , 2 , 3 , 4 ]. After the first isolation, FeMV has been worldwide detected in other countries from Far East as Japan, Thailand, Malaysia, mainland China but also in Turkey, Italy, Germany, UK, USA, Chile and Brazil [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Molecular prevalence reported ranged between 2.7% and 50.8% in urine [ 2 , 3 , 6 , 8 , 9 , 12 , 13 , 14 , 16 , 18 , 20 , 24 , 25 , 26 ], between nihil and 10% in blood [ 3 , 8 , 26 ], between 2.7% and 80% in kidney tissues [ 2 , 6 , 8 , 16 , 20 , 26 ], while seroprevalence was between 18.9% and 66.7% [ 2 , 3 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, feline morbillivirus (FeMV) was isolated for the first time from stray cats ( Felis silvestris catus ) in Hong Kong [ 1 , 2 , 3 , 4 ]. After the first isolation, FeMV has been worldwide detected in other countries from Far East as Japan, Thailand, Malaysia, mainland China but also in Turkey, Italy, Germany, UK, USA, Chile and Brazil [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Molecular prevalence reported ranged between 2.7% and 50.8% in urine [ 2 , 3 , 6 , 8 , 9 , 12 , 13 , 14 , 16 , 18 , 20 , 24 , 25 , 26 ], between nihil and 10% in blood [ 3 , 8 , 26 ], between 2.7% and 80% in kidney tissues [ 2 , 6 , 8 , 16 , 20 , 26 ], while seroprevalence was between 18.9% and 66.7% [ 2 , 3 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese strains were genetically divergent, as they shared a nucleotide identity between 90.6% and 96.8% [ 11 ]. FeMVs genotype 1 were reported in cats from Malaysia [ 27 ] and Thailand [ 17 ], with strains from Malaysia showing a high nucleotide sequence identity (99%) with other Asian FeMVs (Thailand, Japan, and Hong Kong) [ 27 ]. Likewise, phylogenetic analysis of FeMV strains from Thailand revealed that they clustered with those reported in Hong Kong and Japan, sharing the highest nucleotide identity with FeMV strains SS3 and M252A (97.98–98.5% and 97.5–98.3%, respectively) [ 17 ].…”
Section: Genetic Heterogeneity Of Femvsmentioning
confidence: 99%
“…However, a different localization as well as the absence of a significant association with the FeMV antigens was reported [ 13 ]. On the other hand, different studies failed to report a statistically significant association with kidney disease [ 10 , 15 , 16 , 17 , 21 , 22 , 23 , 24 , 28 ]. Several reasons can explain these controversial findings.…”
Section: Femv As the Causative Agent Of Renal Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, a new paramyxovirus was discovered in domestic cats from Hong Kong, and received the name feline morbillivirus (FeMV-1, formerly known as FmoPV) [14]. Initially, the virus was described to be associated with tubulointerstitial nephritis but subsequently, detection of the virus in Europe [14][15][16][17], Asia [18][19][20][21] and the Americas [22,23] showed that the situation is more complex, as some authors found a connection to urinary tract disease, while others did not. Furthermore, a second genotype of FeMV, now designated as FeMV-2, was detected in domestic cats from Germany.…”
Section: Introductionmentioning
confidence: 99%